(untitled) (Medical Forum Monthly, 2024)
Background: Viral hepatitis is a global issue. Hepatitis C virus is worldwide public health problem. This is related to the continued occurrence of new infections and the presence of a large reservoir of chronically infected population. Objective: To observe the frequency of Hepatitis C virus (HCV) infection and find out the risk factors in general surgical patients. Study Design: Prospective Observational type. Place and Duration of Study: This study was carried out in the Surgical Department of Ghulam Muhammad Mahar Medical College Teaching Hospital KhairPur Sindh during one year period from May 2012 to April 2013. Materials and Method: All patients admitted in surgical department either for emergency or elective surgery was included in the study. All patients were screened for HbSAg and Anti-HCV by using immumochromatography (ICT) method. The data of sero-positive patients for hepatitis C were taken for further study. The data was collected through pre- designed Performa and analyzed through SPSS version 15. Results: Total 1030 patients were admitted in surgical department for emergency or elective surgery. During screening Anti-HCV +ve was found in 165(16.0%) patients. Out of these, 95(9.2%) were male and 70 (6.7%) were female. Mean age of these patients was 40.7 years. Among positive patients, most belongs to rural area with poor socioeconomic status. Multiple injections by quacks, shaving by barbers, history of blood transfusion, previous surgery were found to be risk factors in male, while in female history of Gynae and obstetrics procedure, partner +ve for HCV, blood transfusion were found main risk factor. No any risk factor was found in 20 (12.1%) male and 35 (21.2%) females. Conclusion: In the absence of any vaccine for Hepatitis C virus, emphasis should be made on health education and about the risk factors for virus transmission. Health care providers must be committed in the formulation of policies and strict adherence to the safe practices.